Montreal Protocol's impact on the ozone layer and climate - Egorova, Tatiana; Sedláček, Jan; Sukhodolov, Timofei; Karagodin-Doyennel, Arseniy; Zilker, Franziska; Rozanov, Eugene (Copernicus, 2023)
It is now recognized and confirmed that the ozone layer shields the biosphere from dangerous solar UV radiation and is also important for the global atmosphere and climate. The observed massive ozone depletion forced the introduction of limitations on the production of halogen-containing ozone-depleting substances (hODSs) by the Montreal Protocol and its amendments and adjustments (MPA). Previous research has demonstrated the success of the Montreal Protocol and increased public awareness of its necessity. In this study, we evaluate the benefits of the Montreal Protocol on climate and ozone evolution using the Earth system model (ESM) SOCOLv4.0 (modeling tools for studies of SOlar Climate Ozone Links) which includes dynamic modules for the ocean, sea ice, interactive ozone, and stratospheric aerosol. Here, we analyze the results of the numerical experiments performed with and without limitations on the ozone-depleting substance (ODS) emissions. In the experiments, we have used CMIP6 (Coupled Model Intercomparison Project) SSP2-4.5 and SSP5-8.5 (Shared Socioeconomic Pathway) scenarios for future forcing behavior. We confirm previous results regarding catastrophic ozone layer depletion and substantial climate warming in the case without MPA limitations. We show that the climate effects of MPA consist of additional global-mean warming by up to 2.5 K in 2100 caused by the direct radiative effect of the hODSs, which is comparable to large climate warming obtained with the SSP5-8.5 scenario. For the first time, we reveal the dramatic effects of MPA on chemical species and cloud cover. The response of surface temperature, precipitation, and sea-ice fields was demonstrated for the first time with the model that has interactive tropospheric and stratospheric chemistry. We have found some differences in the climate response compared to the model with prescribed ozone, which should be further addressed. Our research updates and complements previous modeling studies on the quantifying of MPA benefits for the terrestrial ...